The effectiveness of a dry-land shoulder rotators strength training program in injury prevention in competitive swimmers - Batalha, N.; Paixao, C.; Silva, A. J.; Costa, M. J.; Mullen, J.; Barbosa, T. M. (Journal of Human Kinetics, 2020)
Competitive swimmers usually undergo large mileage of daily training, in which propulsive force is produced mainly by the upper limbs. Some studies claim that dry-land shoulder rotators injury prevention programs before the in-water swim practice are paramount. However, the effect of shoulder strengthening prior to water training is unclear. This study aimed to analyse the acute effects of training programs conducted on dry land with the goal of preventing shoulder rotators injuries. A group of young swimmers (N = 23) was recruited to participate in this research. The peak torques of shoulder internal and external rotators were assessed before and after the completion of the compensatory strength training program. The isokinetic assessment was performed using two different protocols: 3 repetitions at 60º/s and 20 repetitions at 180º/s. Except for a trivial reduction in strength after the training program, there were no other significant differences in any of the studied variables (shoulders rotators endurance, strength and muscle balance). All results showed trivial to small effect sizes. Our findings suggest that a compensatory strength training program does not have a significant acute effect on the strength, endurance and muscle balance of shoulder rotators in young swimmers. Key words: swimming, isokinetic strength, shoulder rotators